Traditional agroforestry systems practiced in sub-tropical region of Himachal Pradesh - Kumar, Naresh; Kumar, Sanjeev; Verma, K.S. (Indian Journal of Agroforestry, 2020)
A diagnostic survey was carried out to identify the traditional agroforestry systems in sub-tropical region of Himachal Pradesh. The region was dominated by the marginal category of farmers (67.50%) but, the practice of retaining multipurpose trees in the farms was in vogue. Seven agroforestry system types viz., agrisilviculture (AS), agrihorticulture (AH), agrisilvihorticulture (ASH), agrihortisilviculture (AHS), pastoral silviculture (PS), pastoral silvihorticulture (PSH) and pastoral hortisilviculture (PHS) were prevalent in the study area. Among forest tree species Grewia optiva Drumm. ex Burr, Leucaena leucocephala L. Benth, Toona ciliata M. Roem., Albizia lebbek Benth., Acacia catechu Willd., EucalyptusÂ sp., Pinus roxburghii Sargent. and Bauhinia variegata Linn.; and among fruit crops mango, banana and lemon were dominant in different agroforestry system types. Agrisilviculture (AS) and pastoral silviculture (PS) were among the dominant agroforestry systems in the study area.